Lipopolysaccharide Inhibits Alpha Epithelial Sodium Channel Expression via MiR-124-5p in Alveolar Type 2 Epithelial Cells. (3rd March 2020) - Ding, Yan; Cui, Yong; Zhou, Zhiyu; Hou, Yapeng; Pang, Xining; Nie, Hongguang
Abstract : Mesenchymal stem cells (MSCs) have been a potential strategy in the pretreatment of pulmonary diseases, while the mechanisms of MSCs-conditioned medium (MSCs-CM) involved with microRNAs on the regulation of lung ion transport are seldom reported. We investigated the role of miR-124-5p in lipopolysaccharide-involved epithelial sodium channel (ENaC) dysfunction and explored the potential target of miR-124-5p. We observed the lower expression of miR-124-5p after the administration of MSCs-CM, and the overexpression or inhibition of miR-124-5p regulated epithelial sodium channel α -subunit ( α -ENaC) expression at protein levels in mouse alveolar type 2 epithelial (AT2) cells. We confirmed that α -ENaC is one of the target genes of miR-124-5p through dual luciferase assay and Ussing chamber assay revealed that miR-124-5p inhibited amiloride-sensitive currents associated with ENaC activity in intact H441 monolayers. Our results demonstrate that miR-124-5p can decrease the expression and function of α -ENaC in alveolar epithelial cells by targeting the 3′-UTR. The involvement of MSCs-CM in lipopolysaccharide-induced acute lung injury cell model could be related to the downregulation of miR-124-5p on α -ENaC, which may provide a new target for the treatment of acute lung injury.